PENILAIAN KINERJA KEUANGAN PADA PERUSAHAAN ASURANSI - Fina Diana (AkMen JURNAL ILMIAH, 2014)
This study is a descriptive analysis using a qualitative method, which aims to determine the financial performance of companies with economic value added method as one method of calculation of financial performance. Techniques of data collection is carried out by research libraries and documentation. Based on the results of research and discussion, assessment of financial performance begins with a calculation of operating profit after tax was followed by the cost of capital, cost of capital weighted average, and the capital invested., Last of all these values ​​will be used to find the value of economic value added. In terms of the company's internal controls, it is good enough. This is indicated by the separation of duties and responsibilities by each part and full authorization by the Chief of all related documents.